LIQUID-LIQUID EQUILIBRIA OF SOME WATER PLUS TETRAHYDROFURFURYL ALCOHOL PLUS SOLVENT TERNARIES AT 293.2+/-0.1 K AND 101.3+/-0.8 KPA - (:unkn) unknown (ELSEVIER SCIENCE BV, 1995)
Isothermal solubility curves and tie-line end compositions for five water + tetrahydrofurfuryl alcohol + solvent ternaries were experimentally determined at 293.2 +/- 0.1 K and 101.3 +/- 0.8 kPa. Cyclohexanone, 2-methylbutyl ethanoate, 1,2-dichloroethane, 1-octanol and ethyl acetate were used as solvents. Tie-lines were predicted using the LLE-data UNIFAC model. Somewhat acceptable results were obtained for the 1,2-dichloroethane and I-octanol ternaries, whereas the model failed to generate reliable results for the remaining ternaries. Comparison of the extracting capabilities of the investigated solvents were made with respect to distribution coefficients, separation factors and solvent-free selectivity bases.1,2-Dichloroethane and I-octanol exhibited the best solvent performance in the separation of tetrahydrofurfuryl alcohol, especially from its dilute aqueous solutions.
Keywords: EXPERIMENTAL; CHEMICAL EQUILIBRIA; METHODS OF CALCULATION; DATA LLE; PREDICTION